2021
DOI: 10.1111/tid.13569
|View full text |Cite
|
Sign up to set email alerts
|

Association between cytomegalovirus infection and allograft rejection in a large contemporary cohort of heart transplant recipients

Abstract: Background: Cytomegalovirus (CMV) infection remains a common complication after heart transplantation (HTx). The association between CMV infection and allograft rejection is debated in the era of efficient prophylactic antiviral therapies.Methods: This single-center cohort study utilized a highly phenotyped database of HTx recipients (2012)(2013)(2014)(2015)(2016). The primary endpoint was the analysis of the association between CMV infection (CMV load ≥ 500 IU/mL whole blood) and the risk of allograft rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Litjens et al recently reported that donorderived memory-like NKG2C + natural killer cells and Vδ2 neg γδ T lymphocytes could be expanded by CMV replication, and the terminally differentiated TCR αβ + T lymphocytes with poor alloimmunity, NKG2C gene expression, and resistance of the adaptive immune system driven by interferon could be enhanced during CMV infection [51]. These immunological alterations by active CMV replication may be associated with allograft acceptance in kidney, liver, or heart transplant recipients, as well as protection against post-HSCT leukemic relapse in patients with acute myeloid leukemia [27,[51][52][53][54][55][56][57]. Even though further studies are needed to explore more evidence for causal relationships, some studies suggest that CMV infection or disease after transplantation might have beneficial effects to avoid various adverse morbidities or mortality in special recipients [51,58,59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Litjens et al recently reported that donorderived memory-like NKG2C + natural killer cells and Vδ2 neg γδ T lymphocytes could be expanded by CMV replication, and the terminally differentiated TCR αβ + T lymphocytes with poor alloimmunity, NKG2C gene expression, and resistance of the adaptive immune system driven by interferon could be enhanced during CMV infection [51]. These immunological alterations by active CMV replication may be associated with allograft acceptance in kidney, liver, or heart transplant recipients, as well as protection against post-HSCT leukemic relapse in patients with acute myeloid leukemia [27,[51][52][53][54][55][56][57]. Even though further studies are needed to explore more evidence for causal relationships, some studies suggest that CMV infection or disease after transplantation might have beneficial effects to avoid various adverse morbidities or mortality in special recipients [51,58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The IR for CMV in lung transplantation may be underestimated due to the exclusion of CMV syndrome in our study. However, all previous studies presenting CMV epidemiology with percentage did not assess IR, taking into consideration the follow-up duration [21][22][23][24][25][26][27][28][29]31]. This first analysis assessing direct comparison of CMV IRs according to transplant organs in a specific cohort showed that liver or lung transplant recipients had lower IRs for CMV, and heart transplant recipients had the highest IRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more, viral infections such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection could cause acute biventricular heart failure symptoms following a post-myocarditis state in a heart transplantation recipient [67]. Fortunately, regarding viral infections, a large contemporary cohort study on heart transplant recipients demonstrated that cytomegalovirus infection was not associated with cardiac allograft rejection [68]. However, a retrospective cohort study from 2000 to 2009 on 966 patients who underwent heart transplantation depicted that renal replacement therapy and allograft rejection were related to invasive fungal and mold infections [69].…”
Section: Deep Sternal Wound Infection and Other Infectionsmentioning
confidence: 99%